Enhancing Mathematical Fluency in the Elementary Classroom - Leichter, Jessica A. (My University, 2015)
The purpose of this research was to investigate mathematical fluency in a third grade classroom by using a game involving multiplication. We evaluated how students solved these problems and what strategies they used to better understand their level of knowledge and if they have reached mathematical fluency. In order to determine the purpose of my research, I first asked myself what kinds of questions I would like answered about fluency. The first question I wanted to know was “are the strategies students choose very similar or are they inventive?” I felt this question would be answered through data analysis. The next two questions I had were “why do students choose the strategies they do?” and “are students more apt to work out the problem using arithmetic or use a strategy and which do they prefer?” These questions could be answered through personal interviews with the students after the lesson. The last question I had was “how can teachers expand students’ use of strategies?” This question would be answered through my review of literature.